Barriers to first time parent groups: A qualitative descriptive study. (19th June 2018) - Barrett, Norma; Hanna, Lisa; Fitzpatrick, Owen Vincent
Abstract: First‐time parents' groups are offered to new parents in Australia to support their transition to parenthood. Not all parents avail of the service, some cease attendance, and fathers are under‐represented. In the present descriptive, qualitative study, we examined first‐time mothers' perspectives on the barriers to parental participation in the groups. Semi‐structured interviews were conducted with a sample of eight first‐time mothers in a regional city in Victoria, Australia. Interviews revealed groups were perceived as sites strongly reinforcing traditional social norms of parenting. From this central theme, six gendered subthemes emerged as barriers to attendance. Barriers to mothers included non‐normative mothering narratives, such as experiencing stillbirth or having a disabled child, perceived dissonance in parenting ethos, and group size. Barriers to fathers, as perceived by mothers, included groups as female spaces, dads as a minority, and female gatekeeping. A multi‐faceted approach is required to change the common perception that groups are for mothers only. Groups need to be more inclusive of different parenting experiences and philosophies. Segregated groups might better address the needs of both parents. Further research is required to capture fathers' perspectives.